2021
DOI: 10.2147/jir.s330499
|View full text |Cite
|
Sign up to set email alerts
|

Curcumae Ameliorates Diethylnitrosamine-Induced Hepatocellular Carcinoma via Alteration of Oxidative Stress, Inflammation and Gut Microbiota

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) increased the risk factor of hepatocellular carcinoma (HCC). NAFLD induces the hepatic-related cancer deaths mostly in middle-aged men. NAFLD enhanced the inflammatory reaction and oxidative stress in the hepatic tissue. Curcumae exhibited the anti-inflammatory and antioxidant effects. In this study, we made an attempt to scrutinize the protective effect of curcumae on obesity-induced HCC via alteration of inflammation, oxidative stress and gut microbiota. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…, 2019). These free radicals increased lipid peroxidation, suppressed antioxidant enzyme activity and increased the number of toxic metabolites such as 4-hydroxynonenal and MDA (Zhang et al. , 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…, 2019). These free radicals increased lipid peroxidation, suppressed antioxidant enzyme activity and increased the number of toxic metabolites such as 4-hydroxynonenal and MDA (Zhang et al. , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…DEN was metabolized in the liver by P450 monooxygenase, resulting in active ethyl radicals (Mansour et al, 2019). These free radicals increased lipid peroxidation, suppressed antioxidant enzyme activity and increased the number of toxic metabolites such as 4-hydroxynonenal and MDA (Zhang et al, 2021).…”
Section: Lipid Peroxidation Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the levels of IL-6, TNF-α, and IL-1β in mouse serum with liver cancer are significantly higher than those in normal mice and are positively correlated with the degree of malignancy of the tumors. 27,28 Therefore, they can be used as important indicators for screening and evaluating the prognosis of liver cancer. Cell experimental results in vitro showed that SA could significantly reduce the levels of inflammatory factors (TNF-α, IL-6, IL-1β, and IFN) in HepG2 cells and increase the levels of anti-inflammatory factors (IL-10), with statistical significance ( P < .05), which was mutually supported by the results of network pharmacology.…”
Section: Discussionmentioning
confidence: 99%